Examining psychological correlates of vaccine hesitancy: a comparative study between the US and Israel - Simonovic, Nicolle; Gesser-Edelsburg, Anat; Taber, Jennifer M. (Frontiers in Public Health, 2025)
It is important to identify psychological correlates of vaccine hesitancy, including among people not from the United States (U.S.). College students were recruited between March–June 2023 in the US (n = 330, Mage = 20.21, 79.5% female) and in Israel (n = 204, Mage = 23.45, 92.6% female) to complete a cross-sectional survey on vaccine attitudes, emotions, and behavior. A 2 (Nation: US, Israel) × 2 (Vaccine Status: Vaccinated, Unvaccinated) factorial design was used. Individual ANCOVAS controlling for sociodemographic factors were conducted to test main effects of nation and vaccine status, and their interaction, across various psychological correlates of health behavior. Consistent with hypotheses, unvaccinated (vs. vaccinated) individuals reported higher perceived ambiguity, reactance, and anger as well as perceived lower susceptibility, severity, worry, and intentions to vaccinate. Unvaccinated (vs. vaccinated) individuals also reported lower positive emotion. Contrary to hypotheses, unvaccinated individuals reported greater fear. Israeli (vs. American) participants reported higher perceived ambiguity, worry, fear, and anger, as well as lower perceived susceptibility. Vaccinated Americans reported higher intentions to vaccinate again in the future (M = 2.89, SE = 0.08) compared to vaccinated Israelis (M = 2.36, SE = 0.08). However, unvaccinated Americans reported lower intentions to vaccinate (M = 1.80, SE = 0.15) than unvaccinated Israelis (M = 1.95, SE = 0.21). Findings provide insight into correlates to target for vaccine promotion and emphasize the need for cultural tailoring.